Quantitative assessment of brain shifting in the late phase postevacuation in unilateral and bilateral chronic subdural hematomas. (2nd July 2016) - Lin, Muh-Shi; Chang, Cheng-Jen; Lin, Chai-Ching; Chen, Shuo-Tsung; Hwang, Betau; Lu, Shing-Hwa
Abstract : Aim of the study: Recurrence is more common in bilateral chronic subdural hematomas (CSDHs) than in unilateral. Our aim was to quantitatively compare the late phase of brain shifting postevacuation in unilateral and bilateral CSDHs. Materials and Methods: We reviewed computed tomography (CT) scans and medical records of consecutive patients with CSDHs who underwent burr hole drainage. CT scan images (preoperative and postoperative days [PODs] 30 and 60) were imported to Adobe Photoshop, and temporal and spatial changes in brain shifting between PODs 30 and 60, and also the subdural space on POD 60, were analyzed. Results: The bilateral group exhibited a significantly greater late phase of brain shifting than the unilateral group between PODs 30 and 60 ( P < 0.001). The median late phase of brain shifting of the bilateral group was 8.9 mm (interquartile range [IQR]: 8.3–9.0 mm) between PODs 30 and 60, while that of the unilateral group was 1.8 mm (IQR: 1.3–2.5 mm). Conclusions: The postevacuation late phase of brain shifting is statistically greater in bilateral CSDHs than in unilateral CSDHs, which might facilitate bridging vein tearing and consequent rebleeding. This may be one factor accounting for the higher recurrence rate of bilateral CSDHs.